1952
DOI: 10.2136/sssaj1952.03615995001600030009x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Calcium‐Magnesium Ratio on the Solubility and Availability of Plant Nutrients

Abstract: The purpose of the present paper is to determine the effect of the Ca‐Mg ratio in solution and in the soil on the solubility and availability of certain plant nutrients. In recent years many papers have been published on the effect of the Ca‐Mg ratio on crop production. Certain papers and unpublished data have indicated that the Ca‐Mg ratio affects the solubility of other plant nutrients, esepecially phosphorus, including some of the minor or trace elements. Nutrient solutions have been made up and mixed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

1954
1954
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
1
8
1
Order By: Relevance
“…These findings agree with the report of Hunter (1949), who indicated that the exchangeable Ca/Mg ratio in the soil had no effect on the yield of alfalfa but affected the uptake of Ca and Mg. It also corroborates the finding of Sanik (1952), who observed that varying the Ca/Mg exchangeable ratio produced only small yield differences. However, maize plants in many plots in the two distinct locations exhibited Mg-deficiency symptoms, but yields were not significantly affected.…”
Section: Effect Of Soil Ca/mg Ratiosupporting
confidence: 91%
“…These findings agree with the report of Hunter (1949), who indicated that the exchangeable Ca/Mg ratio in the soil had no effect on the yield of alfalfa but affected the uptake of Ca and Mg. It also corroborates the finding of Sanik (1952), who observed that varying the Ca/Mg exchangeable ratio produced only small yield differences. However, maize plants in many plots in the two distinct locations exhibited Mg-deficiency symptoms, but yields were not significantly affected.…”
Section: Effect Of Soil Ca/mg Ratiosupporting
confidence: 91%
“…The optimal Ca to Mg ratio should be 7:1 [76]. According to Sanik et al [77], the Ca:Mg ratio has an impact on the solubility of cations in the soil solution. In our studies, the soil was very low in Mg and although it was not possible to obtain such favourable relations, the introduction of both mineral fertilisation and the digestate, especially a higher dose, resulted in a clear narrowing of the Ca:Mg ratio from 15:1 to 11.5-11.0:1.…”
Section: Soil Propertiesmentioning
confidence: 99%
“…Calcium can interact with the uptake of other ions, including P. For example, it inhibits the translocation of manganese (Mn) to the leaves of barley, and thus reduces Mn-toxicity symptoms (Alam et al 2006) or alleviates sodium (Na) or aluminium (Al) toxicity by preventing Na + -or Al 3+ -induced disturbances of cellular Ca 2+ -homeostasis (Rengel 1992a, Rengel 1992b. A high Ca supply decreases the P uptake of wheat (Sanik et al 1952), but increases the P-absorption rate of some legumes (Bell et al 1989), and aggravates P-toxicity symptoms of Grevillea cv. 'Poorinda Firebird' (Proteaceae) (Nichols and Beardsell 1981).…”
Section: Introductionmentioning
confidence: 99%